Screening of Indonesian Pythochemicals as Glucagon-Like Peptide-1 Receptor Agonist In Silico in Type-2 Diabetes Mellitus - Humamuddin .; R Aj Sri Wulandari; Yuliana Heri Suselo (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2017)
Background: Prevalence of diabetes mellitus (DM) continues to rise in the world, while DM therapy using oral antidiabetic drug (OAD) was still not effective. GLP-1R agonist was a drug that has been developed because it can lower blood sugar levels without hypoglycemic effect. However, GLP-1R agonists have severe side effects such as pancreatitis, thyroid cancer, and pancreatic cancer. Indonesia has 9,600 herbal plants, some of which have a pharmacological effect that could potentially be developed as a drug. This study aimed to identify the Indonesian pythochemicals that have activity as GLP-1R agonist in silico. Methods: The research was a bioinformatics study which utilized all phytochemicals in HerbalDB that had PubChem access code and met the criteria for Lipinski's rule of five as sample. Truncated Exendin-4 was used as standard compound. The structure of Exendin-4 bound to GLP-1R was obtained from the Protein Data Bank, code: 3C5T. Validation of truncated Exendin-4 with GLP-1R needed to get docking scores and binding site at GLP-1R. Molecular docking between phytochemical compounds with GLP-1R models was done using AutodockVina 1.1.2. Visualization of docking results was done using PyMOL 1.7.4. GLP-1R agonist candidates were analyzed based on binding affinity, binding site similarity, and Lipinski's rule of five criterias. Results: Weighteone and Eupatorin were two selected phytochemicals of the most potentially be GLP-1R agonist based on analysis of docking scores and binding site similarity with truncated Exendin-4. Weighteone and Eupatorin bound to Glu68, Glu127, and Glu128 of GLP-1R. Weighteone had docking scores of -5.12 kcal/mol, -6.22 kcal/mol, and -3.88 kcal/mol lower than truncated Exendin-4. Eupatorin had docking scores of -5.02 kcal/mol, -6 kcal/mol, and -3.58 kcal/mol lower than truncated Exendin-4. Conclusion: Weighteone and Eupatorin were the potential Indonesian phytochemicals that could be a GLP-1R agonist in silico. Future studies using Molecular Dynamics Simulation (MDS) method is required to validate this result. In vitro studies are also needed to evaluate these phytochemicals activity as GLP-1R agonists. Keywords: GLP-1R agonists, Indonesian phytochemicals, molecular docking, diabetes mellitus.